Interrupting Sitting Time with Simple Resistance Activities Lowers Postprandial Insulinemia in Adults with Overweight or Obesity. Issue 9 (23rd August 2019) - Larsen, Robyn; Ali, Hamza; Dempsey, Paddy C.; Grace, Megan; Dillon, Francis; Kingwell, Bronwyn A.; Cohen, Neale; Owen, Neville; Green, Daniel J.; Dunstan, David W.
Abstract : Objective: This study aimed to examine the effects on postprandial glucose and insulin responses of interrupting sitting time with brief bouts of simple resistance activities (SRAs) in adults with overweight or obesity. Methods: Participants ( n = 19) were recruited for a randomized crossover trial involving the following two 6‐hour conditions: (1) uninterrupted sitting or (2) sitting with 3‐minute bouts of SRAs (half‐squats, calf raises, gluteal contractions, and knee raises) every 30 minutes (total duration = 27 minutes). Incremental areas under the curve (iAUC) for glucose, insulin, and insulin:glucose ratio were analyzed as prespecified secondary outcomes using mixed‐effects log‐linear regression adjusted for sex, BMI, treatment order, and preprandial values. Results are reported as multiplicative change (exponentiated coefficient [EC] with 95% CI) relative to the control condition. Results: Glucose iAUC during the SRA condition was not significantly different from the prolonged sitting condition (EC = 0.92; 95% CI: 0.73‐1.16; P = 0.43). However, SRAs lowered the postprandial insulin response by 26% (EC = 0.74; 95% CI: 0.64‐0.85; P < 0.001), and there was a 23% lowering of the iAUC for insulin:glucose (EC = 0.77; 95% CI: 0.67‐0.89; P < 0.001). Conclusions: In adults with overweight or obesity, frequent interruptions to sitting time with SRAs lowered postprandial insulin responses and insulin:glucose. These findings may have implications for mitigating cardiometabolic risk in adults with overweight or obesity who engage in prolonged periods of sitting.